(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2023)
Gili Meno is one of the leading small (gili) tourist islands in North Lombok Regency, West Nusa Tenggara Province. Massive tourism activities have an impact on marine biota, including crabs. This research is to determine the characteristics of the crab family of Xanthidae in the intertidal zone of Gili Meno Beach, North Lombok Regency, West Nusa Tenggara Province. The research was conducted using an exploratory method by measuring the abiotic factors of the aquatic environment which is the habitat of crabs. Based on the research, two species of crab from the family of Xanthidae were obtained: Actaeodes tomentosus and Atergatis floridus. A. tomentosus has a relatively rough carapace while A. floridus has a relatively smooth carapace. Both like habitats with sandy substrates with reefs and coral rubble as protection from predators and waves. Abiotic factors: temperature and pH in the intertidal waters of Gili Meno Beach which are suitable for the growth, development and distribution of the two crab species.